Tumour markers assay serum CA125 and Ca153. A preliminary report of USM experience - Yusof, Marzuki Md; Ismail, Zulkifli; Abbas, Saruddin; Jaafar, Zarina
Cancer is one of the most important medical problems in today's world and in Malaysia it is one of the leading causes of death.Although development of cancer takes a considerable amount of man's life span, it is however possible to detect its early pre-cancerous stage.Death due to cancer may be avoided if detected early and this is usually done by biochemical measurement of tumour markers. Tumour Markers are substances which are related to the presence or progress of a tumour. They include proteins such as enzymes and peptides which are secreted into body fluids by tumours and antigens which are expressed on cell surfaces.In contrast, tumour markers also play a critical role in the monitoring and treatment of patients with cancer. The method employed for this preliminary/pilot study is based on ELISA technique. The CA 125 enzyme immunoassay kit was purchased from TECO USA which uses a monoclonal antibody.It is specific for surface antigen derived from a papillary serous cyst adenocarcinoma. Elevated CA 125 serum levels are also found in patient with serious endometrium and fallopian tube.